The Word as Creation and Destruction in the Novel Una niña que no quería vivir - Rojas Porras, Marta (2026)
This essay analyzes the creative and destructive power of language in the construction of female subjectivity, and its role as a tool of resistance against patriarchal violence, in the novel Una niña que no quería vivir (A Girl Who Did Not Want to Live) by Paula López Gamboa (2025), an autobiographical work. The objective is to reflect on the symbolic power of the word in this text, highlighting how contemporary Costa Rican feminist literature transforms the experience of violence and silence into memory, denunciation, and the possibility of emancipation.